2019
DOI: 10.3389/fphys.2019.00816
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptomic Model of Postnatal Cardiac Effects of Prenatal Maternal Cortisol Excess in Sheep

Abstract: In utero treatment with glucocorticoids have been suggested to reprogram postnatal cardiovascular function and stress responsiveness. However, little is known about the effects of prenatal exposure to the natural corticosteroid, cortisol, on postnatal cardiovascular system or metabolism. We have demonstrated an increased incidence of stillbirth in sheep pregnancies in which there is mild maternal hypercortisolemia caused by infusion of 1 mg/kg/d cortisol. In order to model corticosteroid effects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…The stillbirth rate was reported to increase with higher levels of cortisol in pregnant sheep ( Antolic et al., 2019 ). In our study, the WA group had lower saliva concentrations of pre-prandial cortisol than the control diet group, which contributed to the reduction or downward trend for the stillbirth rate in the 15% and 30% WA groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The stillbirth rate was reported to increase with higher levels of cortisol in pregnant sheep ( Antolic et al., 2019 ). In our study, the WA group had lower saliva concentrations of pre-prandial cortisol than the control diet group, which contributed to the reduction or downward trend for the stillbirth rate in the 15% and 30% WA groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This time was chosen in order to reliably get fetal data prior to the onset of labor. Transcriptomic data [21] from hearts at this age of gestation suggest changes in cardiac metabolism in the model studied in our lab (chronic maternal stress/hypercortisolemia), and so this age was our starting point for establishing the stable isotope tracer method for use in subsequent studies. Additionally, since the ewes used in the study were not in labor yet, the observed metabolic fluxes are not labor contraction stimulated changes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a high concentration of maternal cortisol throughout late gestation alters the regular cardiac gene expression pattern in the ovine foetus [230,231], which persists into postnatal development. Transcriptomic profile of lipid metabolism, cell proliferation and cardiac remodelling, are affected postnatally after the in utero cortisol exposure, together with increased cardiac wall thickness and altered glucose metabolism [232]. These alterations may cause postnatal cardiac hypertrophy and altered responses to oxidative stress [232].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Transcriptomic profile of lipid metabolism, cell proliferation and cardiac remodelling, are affected postnatally after the in utero cortisol exposure, together with increased cardiac wall thickness and altered glucose metabolism [232]. These alterations may cause postnatal cardiac hypertrophy and altered responses to oxidative stress [232]. In addition to higher cortisol release, stress triggers the increase of norepinephrine and inflammation, which affect the foetal environment and lead to infant health complications.…”
Section: Glucocorticoidsmentioning
confidence: 99%